Development of a radiofrequency ablation platform in a clinically relevant murine model of hepatocellular cancer - Qi, Xiaoqiang (Cancer Biol Ther, 2015)
RFA is used in treatment of patients with hepatocellular cancer (HCC); however, tumor location and size often limit therapeutic efficacy. The absence of a realistic animal model and a radiofrequency ablation (RFA) suitable for small animals presents significant obstacles in developing new strategies. To establish a realistic RFA platform that allows the development of effective RFA-integrated treatment in an orthotopic murine model of HCC, a human cardiac radiofrequency generator was modified for murine use. Parameters were optimized and RFA was then performed in normal murine livers and HCCs. The effects of RFA were monitored by measuring the ablation zone and transaminases. The survival of tumor-bearing mice with and without RFA was monitored, ablated normal liver and HCCs were evaluated macroscopically and histologically. We demonstrated that tissue-mimicking media was able to optimize RFA parameters. Utilizing this information we performed RFA in normal and HCC-bearing mice. RFA was applied to hepatic parenchyma and completely destroyed small tumors and part of large tumors. Localized healing of the ablation and normalization of transaminases occurred within 7 days post RFA. RFA treatment extended the survival of small tumor-bearing mice. They survived at least 5 months longer than the controls; however, mice with larger tumors only had a slight therapeutic effect after RFA. Collectively, we performed RFA in murine HCCs and observed a significant therapeutic effect in small tumor-bearing mice. The quick recovery of tumor-bearing mice receiving RFA mimics observations in human subjects. This platform provides us a unique opportunity to study RFA in HCC treatment.